2020
DOI: 10.1177/1060028020909388
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of an Association Between UFH Dosing Based on Estimated Blood Volume and Venous Thromboembolism and Bleeding in the Underweight and Critically Ill

Abstract: We undertook a post hoc analysis of study data published in the journal to further investigate the association between bleeding risk and the use of venous thromboembolism (VTE) prophylaxis in underweight, critically ill patients and to optimize its dosing. 1 Given the low volume of distribution and 1-compartment model of unfractionated heparin (UFH), dosing based on estimated blood volume (EBV) could be used to improve safety and efficacy. Clinical utility has been suggested with this strategy in a previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The prevalence of clinically relevant VTE and bleeding in this study was consistent with similar analyses of low-weight and critically ill patients. 8,9,13,14 The prevalence of clinically relevant VTE was similar to that in contemporary analyses of trauma patients (0.5% vs 1.1%-1.9%), but the prevalence of clinically relevant bleeding was higher (6.9% vs 2.3%-4%). 4,7,21-23 This supports previous assertions that low-weight critically ill patients may be at risk of bleeding if prescribed what are considered “standard” or non–weight-adjusted VTE prophylaxis regimens.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The prevalence of clinically relevant VTE and bleeding in this study was consistent with similar analyses of low-weight and critically ill patients. 8,9,13,14 The prevalence of clinically relevant VTE was similar to that in contemporary analyses of trauma patients (0.5% vs 1.1%-1.9%), but the prevalence of clinically relevant bleeding was higher (6.9% vs 2.3%-4%). 4,7,21-23 This supports previous assertions that low-weight critically ill patients may be at risk of bleeding if prescribed what are considered “standard” or non–weight-adjusted VTE prophylaxis regimens.…”
Section: Discussionsupporting
confidence: 67%
“…In current literature, EBV has shown promise as a potential dose modifier for UFH in low-weight critically ill patients after suggesting a higher risk of clinically relevant bleeding with increased daily doses per milliliter of EBV in 2 separate analyses. 13,14 In addition, a recently published study in trauma patients with a mean BMI of 27.4 kg/m 2 found that enoxaparin dose (in mg) per liter of EBV was more closely correlated with recorded anti-Xa concentrations than enoxaparin dose per total body weight (TBW) or BMI. 7 Estimated blood volume has not been formally studied as a potential dose modifier in low-weight trauma patients to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current study, BMI‐based enoxaparin dosing resulted in only 62.6% of patients reaching target anti‐Xa concentrations, which is inadequate. Although not supported by outcome data, EBV‐based dosing represents a theoretically superior strategy because the body composition of a typical trauma patient (young, male, and muscular) results in a larger blood volume, but not necessarily higher BMI 16,17 . This study found that anti‐Xa concentrations correlated better with EBV than to BMI and TBW.…”
Section: Discussionmentioning
confidence: 63%
“…24 However, in a study of low-weight trauma patients weighing <60 kg, enoxaparin dose-per-unit EBV was not different between patients who did or did not bleed, and was not a significant predictor of bleeding in a logistic regression analysis. 39 With an increased sample size and broader population, our results also demonstrated that patients dosed using the EBV-based strategy had the highest percentage of anti-Xa levels at goal, but our study was not powered to detect any difference in bleeding or VTE. In pairwise comparison, the EBV dosing strategy was more than three times as likely to yield anti-Xa levels at or above target compared to BMI dosing strategy.…”
Section: Discussionmentioning
confidence: 69%
“…In one single‐center study with 241 trauma patients, patients dosed using an EBV‐based enoxaparin guideline were more likely to achieve target anti‐Xa levels 0.2–0.5 IU/mL compared to BMI‐based dosing (81% vs. 63%, aOR 2.02) 24 . However, in a study of low‐weight trauma patients weighing <60 kg, enoxaparin dose‐per‐unit EBV was not different between patients who did or did not bleed, and was not a significant predictor of bleeding in a logistic regression analysis 39 . With an increased sample size and broader population, our results also demonstrated that patients dosed using the EBV‐based strategy had the highest percentage of anti‐Xa levels at goal, but our study was not powered to detect any difference in bleeding or VTE.…”
Section: Discussionmentioning
confidence: 85%